2020
DOI: 10.1155/2020/1921609
|View full text |Cite
|
Sign up to set email alerts
|

GFAT1/HBP/O-GlcNAcylation Axis Regulatesβ-Catenin Activity to Promote Pancreatic Cancer Aggressiveness

Abstract: Reprogrammed glucose and glutamine metabolism are essential for tumor initiation and development. As a branch of glucose and metabolism, the hexosamine biosynthesis pathway (HBP) generates uridine diphosphate N-acetylglucosamine (UDP-GlcNAc) and contributes to the O-GlcNAcylation process. However, the spectrum of HBP-dependent tumors and the mechanisms by which the HBP promotes tumor aggressiveness remain areas of active investigation. In this study, we analyzed the activity of the HBP and its prognostic value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…PDAC is a well-known glutamine-addicted cancer and is extremely sensitive to glutamine deprivation [18]. GFPT1/ HBP functions as a coordinator of glucose and glutamine metabolism and is upregulated in various types of cancer [14]. A recent study indicated that oncogenic KRAS signaling, induced by a signature mutation in PDAC, markedly augmented the flux of HBP by inducing the expression of GFPT1 [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDAC is a well-known glutamine-addicted cancer and is extremely sensitive to glutamine deprivation [18]. GFPT1/ HBP functions as a coordinator of glucose and glutamine metabolism and is upregulated in various types of cancer [14]. A recent study indicated that oncogenic KRAS signaling, induced by a signature mutation in PDAC, markedly augmented the flux of HBP by inducing the expression of GFPT1 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that high expression of GFPT1 correlated with unfavorable prognosis in hepatocellular carcinoma [13]. A recent study suggested that inhibiting GFPT1 expression via pharmaceutical inhibitors or genetic silencing may result in reduced cell proliferation and cancer invasiveness [14]. However, the correlation between GFPT1 gene expression and clinical outcomes of resectable PDAC patients remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These two enzymes are essential for the first few steps of glycan biosynthesis; thus, a differential expression of genes encoding them may show differences in the degree of cell glycosylation as well as a possible switch of glucose metabolism to the HBP pathway. Furthermore, the skin cutaneous melanoma has shown the upregulation of the HBP pathway activity as well as single HBP components in comparison with the normal skin (Jia et al 2020 ). On the other hand, the most important enzymes responsible for the N -glycan branching are GnT-III (encoded by gene MGAT3 ), GnT-IV (encoded be two genes MGAT4a and MGAT4b ), GnT-V (encoded by gene MGAT5 ), GnT-IX (encoded by gene MGAT9 ), Fut8 (encoded by gene FUT8 ) and GCNT2 (Taniguchi and Kizuka 2015 ; Harada et al 2019 ; Dimitroff 2019 ).…”
Section: Methodology Used For Investigating Changes In Melanoma Signaling Pathwaysmentioning
confidence: 99%
“…1 ; Nagel and Ball, 2015 ). O -GlcNAc modification of transcription factors, including Sp1, β-catenin, SOX2, FOXO3, and YAP, regulates their nuclear translocation and activity, subsequently promoting gene expression programs that confer proliferative and anti-apoptotic cancer cell phenotypes ( Banerjee et al, 2013 ; Jia et al, 2020 ; Sharma et al, 2019 ; Shin et al, 2018 ; Peng et al, 2017 ). Levels of O -GlcNAc are governed by the balance between O -GlcNAc transferase (OGT) and O -GlcNAcase (OGA), which add and remove UDP-GlcNAc to and from acceptor substrates, respectively.…”
Section: Sustaining Proliferative and Pro-tumorigenic Signalingmentioning
confidence: 99%